ISAAC written questionnaire versus incorporating videos before the questionnaire for asthma prevalence among middle schools students in Al-Sharkiya Egyptian Governorate - Osama T. Amer; Hussnia M. Ragab; Shereen M. Bahgat; Sameh A. Elsayed; Marwa Gad; Ahmed Fawzy; Salwa Hegazy; Eman Mokhtar; Hala Yaseen; Dina T. Sarhan (SpringerOpen, 2020)
Abstract Background Asthma is the most common chronic respiratory disorder in childhood with worldwide increasing in its prevalence and global burden. The International Study of Asthma and Allergies in Childhood (ISAAC) provides a standardized methodology to describe the prevalence and severity of childhood asthma symptoms all over the world using simple standardized questionnaires that allow comparisons across geographic and linguistic boundaries. This study aimed to find a suitable application of ISAAC asthma questionnaire to improve the perception and response of the middle (preparatory) school students in Al-Sharkiya Governorate as a step to update the Egyptian prevalence of asthma among children through the translation of the ISSAC written questionnaire into Arabic and to compare the student's response to the translated questionnaire with their response to the same questionnaire after showing ISAAC videos. Results The percentage of student's positive answers for asthma symptoms in the written questionnaire after watching ISAAC videos was significantly lower when compared to their written questionnaire answers without watching videos with no significant agreement between the student's answers in the two methods. Conclusion Using ISAAC videos before filling the written questionnaire improved the students' understanding of and dealing with the written questionnaire.